192k views
4 votes
Math algebra two plz show your work

Math algebra two plz show your work-example-1
User Clonk
by
5.0k points

1 Answer

4 votes

Answer:

The answer is
b=3, a=-2, and
c=3.

Explanation:

To solve this system of equations, start by solving for (a) in the third equation.

To solve for (a) in the third equation, add
3b to both sides of the equation, which will look like
2a=-13+3b\\-a+b-c=2\\2a+3b-4c=-7. Next, divide each term in
2a=-13+3b by 2 and simplify, which will look like
(2a)/(2)=(-13)/(2) +(3b)/(2) \\-a+b-c=2\\2a+3b-4c=-7 =
a=(-13)/(2) +(3b)/(2) \\-a+b-c=2\\2a+3b-4c=-7.

Then, replace all variables of (a) with
-(13)/(2) +(3b)/(2) in each equation and simplify, which will look like
-13+6b-4c=-7\\-(2c-13+b)/(2)=2\\a=-(13)/(2)+(3b)/(2).

The next step is to reorder
-(13)/(2) and
(3b)/(2), which will look like
(3b)/(2)-(13)/(2)\\-13+6b-4c=-7\\-(2c-13+b)/(2) =2.

Then, solve for (b) in the second equation. To solve for (b) in the second equation start by moving all terms not containing (b) to the right side of the equation, which will look like
6b=6+4c\\a=(3b)/(2)-(13)/(2) \\-(2c-13+b)/(2) =2. Next, divide each term in (
6b=6+4c) and simplify, which will look like
b=1+(2c)/(3) \\a=(3b)/(2) -(13)/(2\\)\\-(2c-13+b)/(2) =2.

Then, replace all variables of (b) with
1+(2c)/(3) in each equation and simplify, which will look like
-(2(2c-9))/(3)=2\\a=c-5\\b=1+(2c)/(3).

The next step is to solve for (c) in the first equation. To solve for (c) in the first equation start by multiplying both sides of the equation by
-(3)/(2) and simplify, which will look like
2c-9=-3\\a=c-5\\b=1+(2c)/(3). Then, move all terms not containing (c) to the right side of the equation, which will look like
2c=6\\a=c-5\\b=1+(2c)/(3). Next, divide each term in
2c=6 by 2 and simplify, which will look like
c=3\\a=c-5\\b=1+(2c)/(3).

Then, replace all variables of (c) with 3 in each equation and simplify, which will look like
b=3\\a=-2\\c=3. Finally, the list of all the solutions are
b=3,a=-2, and
c=3.

User Gtovar
by
5.3k points